New record of a very specialized interaction: myrcidris epicharis Ward 1990 (Pseudomyrmecinae) and its myrmecophyte host Myrcia madida McVaugh (Myrtaceae) in Brazilian Meridional Amazon - Vicente,Ricardo Eduardo (2012)
In this study we present a new record of a plant-animal interaction: the mutualistic relationship between the specialist plant-ant Myrcidris epicharis Ward, 1990 (Pseudomyrmecinae) and its myrmecophyte host Myrcia madida McVaugh (Myrtaceae). We observed more than 50 individuals of M. madida occupied by M. epicharis in islands and margins of the Juruena River, in Cotriguaçu, Mato Grosso, Brazil (Meridional Amazon). We discuss a possible distribution of this symbiotic interaction throughout all the riparian forest of the Amazon River basin and its consequence to coevolution of the system.